The Moderating Influence of Values on the Relationship between Materialism and Life Satisfaction - V.A. Khashchenko; N.N. Khashchenko (Экспериментальная психология)
In this article, we investigate if and how basic individual values influence the relationship between materialism and life satisfaction. Using regression analysis, we analyze a sample of 184 participants (92 females, 92 male), whose ages ranged from 18 and 59 years, to investigate if the impact of materialism on life satisfaction is moderated by basic values. Data were collected using the Russian version of Schwartz's PVQ-RR individual values questionnaire, the Value Materialism Questionnaire (VMQ) and the Life Satisfaction Scale (SLS). We found that materialism weakly negatively affects life satisfaction and that the strength of this relationship is moderated by higher-order values and meta-values. We tested the moderating effect of these values of materialism separately. We found that only higher-order value Openness to Change well as individual orientation focus meta-value (Self-Enhancement and Openness to Change) that interacted significantly with materialism. Hypotheses about the effects interacting materialism with all other values were included in the model were not confirmed.